Identifikasi Arsitektur Melayu: Rumah Tinggal Tradisional dan Masjid di Semenanjung Malaysia - Zairin Zain; Najwa Amalia Uray; Silvia Christabella (EMARA: Indonesian Journal of Architecture, 2021)
This study aims to describe the influence of the Malay culture and customs on the Malaysian peninsula on the architectural forms of houses and mosques. The discussion is carried out on architectural elements with the object of discussion of houses and mosques. The traditional Malay house has a house topology on stilts with high poles, a layered roof, the primary material with wooden structures, and many openings (ventilations) that illustrate adaptation to the tropical climate. The type of house is determined by its roof shape, namely Bumbung Panjang, Bumbung Limas, Bumbung Perak, and Bumbung Perak Bumbung Limas. On the other hand, a mosque is a very important building for the Malay community because it is a space for congregational prayer and a formal education/teaching center for religious education, and an administrative center for communities. The overall impression of the mosque is described as a building with a flat hypostyle roof. This typology follows a religious concept of Malaysian people regarding many aspects of design on the holiness of mosques designed to develop seven architectural elements